Biodegradation of diphenyl ether and its monohalogenated derivatives by Sphingomonas sp. strain SS3. - Schmidt, S (1992)
The bacterium Sphingomonas sp. strain SS3, which utilizes diphenyl ether and its 4-fluoro, 4-chloro, and (to a considerably lesser extent) 4-bromo derivatives as sole sources of carbon and energy, was enriched from soil samples of an industrial waste deposit. The bacterium showed cometabolic activities toward all other isomeric monohalogenated diphenyl ethers. During diphenyl ether degradation in batch culture experiments, phenol and catechol were produced as intermediates which were then channeled into the 3-oxoadipate pathway. The initial step in the degradation follows the recently discovered mechanism of 1,2-dioxygenation, which yields unstable phenolic hemiacetals from diphenyl ether structures. Oxidation of the structure-related dibenzo-p-dioxin yielded 2-(2-hydroxyphenoxy)-muconate upon ortho cleavage of the intermediate 2,2',3-trihydroxydiphenyl ether. Formation of phenol, catechol, halophenol, and halocatechol from the conversion of monohalogenated diphenyl ethers gives evidence for a nonspecific attack of the dioxygenating enzyme system.